Engaging Beyond Academia: Exploring Non-English Majors' Motivations for English Language Community Participation in Indonesia - Sari, Darmaida; Junaidi, Junaidi (VELES Voices of English Language Education Society, 2024)
This study explores the motivations and experiences of non-English major students participating in an English language community at Institut Syekh Abdul Halim Hasan Binjai, Indonesia, where English proficiency is viewed as a crucial tool for personal, educational, and professional advancement. The research, conducted through in-depth interviews with 18 volunteer participants from diverse academic fields such as Sharia Banking, Sharia Economics, Sharia Economic Law, Family Law, Islamic Education, and Early Childhood Islamic Education, reveals that the English community plays a pivotal role in fostering language development. It provides a supportive and immersive environment that facilitates English practice, boosts confidence, and enhances cultural engagement. Moreover, the findings highlight the significant impact of instructors in motivating students by creating a pressure-free atmosphere and encouraging continuous professional development. The study concludes that English language communities, complemented by tailored instructional strategies, are effective in enhancing English learning for non-English majors, empowering them to meet their varied goals and succeed in global settings.